Conversion Conditions for Fixed Temperature Difference with Variable Water Supply Temperature and Large Temperature Difference Control Strategies in Urban Rail Transit Station Air-conditioning Chilled Water System - XIA Sanxian; ZHANG Shaochen; YU Weizhi; LAN Jie; HE Dasi (Chengshi guidao jiaotong yanjiu, 2024)
Objective To achieve the lowest overall energy consumption of urban rail transit station air-conditioning chilled water system under both fixed temperature difference with variable water supply temperature and large temperature difference conditions, it is necessary to study the conversion conditions between these two control strategies. Method Taking an urban rail transit station in Zhengzhou City as example, a model of air-conditioning chilled water system under the above two conditions is established using TRNSYS (transient system simulation tool) platform. Under the premise of maintaining the required cooling capacity at the terminal end of air-conditioning chilled water system, the impact on system energy consumption is studied in scenarios of a constant chilled water temperature difference with variable water supply temperature (7-12 ℃), and a constant water supply temperature with variable water supply-return temperature difference (5-10 ℃). Result & Conclusion The conversion conditions between the two control strategies are as follows: when the load rate is less than or equal to 40%, the fixed temperature difference with variable water supply temperature control strategy is more energy-efficient; when the load rate exceeds 50%, the large temperature difference control strategy is more suitable. These conversion conditions not only meet the comfort requirements of station personnel, but also achieve the goal of combined control strategy regulation, ultimately reducing the overall energy consumption of air-conditioning chilled water system.